Substrate-Suspended Air Cavity Resonator and Its Application in Low Phase Noise Oscillator - Xu, Jun; Yang, Xiuqiang; Huang, Dan; Chen, Bangchao; Chen, Yang; Guo, Lei; Xiao, Fei (Frontiers in Physics, 2021)
In this paper, a substrate-suspended air cavity resonator featured by high-Q is presented, which consists of five separate layers for confining electromagnetic energy. Its field distribution is analyzed in depth. By appropriately coupling the two ones, a second-order Chebyshev bandpass filter is obtained, and design procedure is described. The filter forms a specific group delay response, in which high values can be achieved within a narrow frequency range around the center frequency. The filter has great flexibility in adjusting its magnitude and phase responses so that low insertion loss and high group delay are achieved simultaneously. Such feature plays an important role in reducing phase noise when it is applied in microwave oscillator. For demonstration, a X-band oscillator example was designed and fabricated. As the measured results show, it works at 11.16 GHz and the phase noise at 100 KHz away from the oscillation frequency is as low as -120.68 dBc/Hz.